PENERAPAN KEBIJAKAN SANKSI PIDANA DALAM PERATURAN DAERAH SEBAGAI UPAYA PENANGGULANGAN KEJAHATAN - Candra Perbawati (Universitas Lampung, 2007)
Policies prevention of crimes and violations in essence defense) and efforts to achieve the welfare of society (social walfare) In the application of the policy of criminal sanctions stipulated in Local Regulation as a means of protection of public interests, the application will succeed, if in the formulation of criminal penalties in accordance with the purpose of punishment, in addition based on the Criminal Code and Law Number 32 of 2004 and other legislationKeywords: Local Regulation, the Regional Criminal Sanction in the Local Regulation